Exploring drivers and levels of technology adoption for ecological intensification of pastoral systems in north Patagonia drylands - Hara, Sofia Maria; Faverin, Claudia; Villagra, Edgar Sebastian; Easdale, Marcos Horacio; Tittonell, Pablo Adrian (Elsevier, 2022)
Although pastoral systems make a significant contribution to food security, they are also pointed out as being responsible for substantial environmental impact. Ecological intensification through process- rather than inputbased technologies has been proposed as a means to achieve economic, environmental, and social win-win situations. We studied structural diversity, technology adoption, farmer´s strategies, and functional attributes (productivity, reproductive efficiency, greenhouse gas emissions, diversification, and self-sufficiency) of pastoral systems in North Patagonia based on interviews of 70 farms with the following objectives: (a) to analyze farm structural characteristics as drivers of technology adoption for ecological intensification, (b) to describe their association with farmers´livelihood strategies, and (c) to explore trade-offs and synergies among functional attributes. An ongoing ecological intensification was revealed based on the adoption of technologies towards animal´s welfare, survival, and overall systems´efficiency, on-farm produced feed (self-sufficiency), and product diversification, promoting nutrient re-cycling within farm boundaries. Four farm types were differentiated by their access to information exchange channels, which together with labor characteristics determined technology adoption and farmers´ strategies. The main strategy of family farms that exhibited low to no hired labor, and intermediate to low access to information, was the diversification of products or incomes. Larger farms, with hired labor and access to information exchange channels, had an entrepreneurial strategy towards increasing production efficiencies. Enteric emission intensity per unit product and area exhibited significant trade-offs with meat production (Spearman ρ = 0.87; Y = 0.459 X + 0.352; R2 = 0.95), and synergies with reproduction efficiency (Spearman ρ = 0.51; Y = 0.013 X + 1.612; R2 = 0.28), respectively. Improving individual animal production instead of per unit area is encouraged to prevent overgrazing and land degradation, searching for win-win’s between emission mitigation and livestock production.